Hubungan Religiusitas Dan Empati Dengan Perilaku Altruistik - Ni'mah, Roudlotun; , Dr. Taufik, M.Si (2014)
This study aims to determine the relathionship between religiosity and empathy with altruistic behavior. Subjects were students in Al-asy'ari boarding school totaling 90 students formalesex-menbetween the ages of12 to25years. Measuring instruments usedarealtruisticbehaviorscale, the scale ofempathyandreligiosityscale. Thedata capture techniquesusingproportionatestratified random sampling. Methods of data analysisusing multiple regression analysiswithSPSS forWindows16.0program. the results showed significant relationship between religiosity and empathy with altruistic behavior. Also there is a significant positive relationship between religiosity with altruistic behavior, and there is a significant positive relationship between empathy and altruistic behavior. Effective contribution of religiosity and empathy to altruistic behavior for 49,2 % indicated by the coefficient of determinant (R²) 49,2. This means there is 50, 8% of other variables that affect students' altruistic behavior.